Personagens e identidades em A Paixão de Ajuricaba, de Márcio Souza - (:unkn) unknown (Universidade Federal do Amazonas, 2012)
The objective of this study is to dialogue with A Paixão de Ajuricaba , theater piece of Márcio Souza, relating to its characters, the way they experience their dramas, relate themselves, make their choices, build and rebuild their identities. This perspective guided the study through the investigation of the tragic aspects of the text, based on the theoretical construction of Pierre Grimal and Rene Girard, and also the Greek philosopher Aristotle and the French Descartes. Approaching the concepts of Passion, it were used the authors Adauto Noves and Maria Luísa Ferreira. Interpretations and discussions detailed in the identity process, using the literary work of the social psychologist Antônio Ciampa, demonstrated that the identity, even fictional, concerning the characters of Ajuricaba, Inhambu, Teodósio e Comandante Português, is metamorphosis and not a static event, and such as the passion, should possess mobility. The identities are not constituted only by the identical, but also based in differences, among which, to be an indian is necessary not to be white, and vice-versa. Results allowed access to new theoretical constructs, unveiling the complexity of the identity process and the importance of artistic and literary works in the Amazon.
Keywords: A Paixão de Ajuricaba; Márcio Souza; Antônio Ciampa; OUTROS